PENGEMBANGAN MODEL PERHITUNGAN NILAI PROTEKSI JALAN SEBAGAI DASAR PEMERINGKATAN BINTANG JALAN NASIONAL DARI PERSPEKTIF PENGENDARA KENDARAAN BERMOTOR RODA EMPAT ATAU LEBIH - Idris, Muhammad (Direktorat Bina Teknik Jalan dan Jembatan, 2024)
This research introduce the SRS which was developed from RPS model for the Indonesian National Road particularly from the perspective of motorists of four or more wheels, which is explored from the characteristics of traffic accidents along Indonesian national roads. This SRS model considers 2 different main parameters as well as 4 main parameters that are the same as the main parameters of the SRS iRAP and with a total of 43 road attributes. The two main parameters that differ from the SRS iRAP model are the rear-end collision parameters and the front-to-side collision accident when turning around. While the same 4 parameters are front-side collision on property access, single accidents off the road, head-on collision, and accidents at intersections. At the initial stage, the INR SRS model was designed using 51 road attributes. After analysing using the IPA methods, 43 road attributes were successfully formulated for the INR SRS model, which consisted of 30 attributes for likelihood factors, 10 attributes for severity factors, 2 attributes for the external traffic influence factors, and 1 attribute for the operational speed factor. This research also succeeded in proving that the INR SRS model is significantly different from the iRAP SRS model. The three main parameters of the INR SRS model, namely rear-end collision accident parameters, front-to-side collision parameters when U-turning, and front-to-side collision accident parameters at property access are significantly different from the parameters of the SRS iRAP model. Keywords: SRS, RPS, traffic accident, national roads, road attribute.